Deep mediatization - Hepp, Andreas (London ; New York : Routledge, 2020)
"Andreas Hepp takes an integrative look at one of the biggest questions in media and communications research: how digital media is changing society. Often, such questions are discussed in isolation losing sight of the overarching context in which they are situated. Hepp has developed a theory of the re-figuration of society by digital media and their infrastructures and provides an understanding of how profound today's media-related changes are, not only for institutions, organizations and communities, but for the individual as well. Rooted in the latest research, this book does not stop at a description of media-related change, instead it raises the normative challenge of what deep mediatization should look like so that it might just stimulate a 'good life' for all. Providing original and critical research, the book introduces mediatization to students of media and cultural studies as well as neighbouring disciplines like sociology, political science and other cognate disciplines"--
OCLC-licensed vendor bibliographic record.
Keywords: Digital media -- Social aspects; Social change; SOCIAL SCIENCE / Media Studies